Study on the Deformation of Pavement Structure with Multiplex Organic Hydraulicity Mixture under Driving Load Based on Simulation and Experiment - Hairong Gu; Lingying Zhao; Min Ye; Zhiyong Li; Xinxin Xu; Xianbao Zuo (Advances in Materials Science and Engineering)
With the continuous growth of global warming and traffic volume, rutting deformation is common on road surfaces. A new type of pavement mixture, a semiflexible mixture, was proposed to solve the easy deformation and low riding quality of traditional pavement mixtures. It can be divided into pouring type and mixing type according to the construction method. However, there is little research on mixed semiflexible mixtures (i.e., multiplex organic hydraulicity (MOH) mixtures) in the current literature, so the deformation of pavement under driving loads was studied based on the MOH mixture in this paper. Four types of pavement composed of the traditional mixture and MOH mixture (i.e., AC13-AC20, AC13-MOH, MOH-MOH, and MOH-AC20) were selected to achieve the purpose of the research. Based on these four types of pavement, the deformation of the pavement was studied by simulations and experiments. The results show that the deformation of the upper layer is almost the same for these four types of pavement and that the deformation of the middle layer changes substantially for these four types of pavement. In regard to the deformation, the relationship is MOH-MOH < AC13-MOH < MOH-AC20 < AC13-AC20. In addition, the contribution rate of the deformation of the middle layer is much greater than that of the upper layer. The antideforming ability of the whole pavement can be improved by using the MOH mixture as the middle layer of the pavement, which means that the performance of the MOH mixture can achieve the best performance when it is applied to the middle layer.